The effect of Zirconia composition on HAp-Zirconia feedstock using Palm Stearin binder system: article - Abd Latiff, Nurul Jannah; Subuki, Istikamah (2017)
The purpose of this study is to investigate the performance of feedstock containing HAp-ZrO₂ bioceramic powder with palm stearin (PS) based binder system. The feedstock was varied with three different weight percentage composition; 90-10, 80-20 and 70-30 of the HAp-ZrO₂ and the optimum powder loading of 60 vol % was remained for each composition. Different weight composition of the HAp-ZrO₂ resulted in different characteristics of the as-mixed powder similarly in their mixing behaviour. Therefore, the performance of HAp-ZrO₂ composite powder is studied through the particle size distribution, pycnometer density and X-ray diffraction (XRD). Then, the influence of ZrO₂ percentage content in the feedstock also is observed via the rheological study. The rheological response of MIM feedstock by means of a capillary rheometer is essential to be carried out in order to examine the viscosity and flow behaviour index of the feedstock. From the analysis, the increasing content of ZrO2 by 30wt% in the feedstock is indeed affecting the mixing behaviour of the asmixed powder as its XRD patterns showed the evident differences in the peak present. In term of rheological study, the 70-30wt% of HAp-ZrO₂ is deemed unfit for MIM processes based on the too high viscosity and too low of n value.